Humor and satire in the press of the Polish community in America (to 1918). An outline - Kiper, Daniel (Laughter, humour, satire, 2024)
The article makes a cross-sectional characterisation of the satirical and humorous press of the Polish diaspora in America between 1886 and 1918. Using selected examples, it shows how the satirical magazines of the Polish diaspora in the United States tried to meet the needs of the mass audience and to influence the public ideologically. The publishers of the Polish diaspora were forced to adapt the humour magazines they published to their vision of the world and the expectations of their audiences. They did not compete with American magazines but tried to find a separate niche in the media macrocosm of the time and develop it independently of the mainstream. To maintain a colloquial style in the media message, an attempt was made to balance linguistic conventions, journalistic forms, and illustrative material in order to be comprehensible not only to the first generation of immigrants but above all to the representatives of the Polish diaspora born in the New World who learnt American humour.